ENHANCEMENT OF DIFFERENTIATED LEARNING EFFICACY VIA ACADEMIC SUPERVISION IN SENIOR HIGH SCHOOL SETTINGS: A COMPREHENSIVE OPTIMIZATION APPROACH - Satiri, Satiri; Fathurrohman, Maman; Yuhana, Yuyu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
This research constitutes a two-cycle School Action Research involving 29 teachers at SMAN 1 Jawilan, Serang, Banten. Employing data collection methods such as observation, field notes, and documentation, coupled with a comprehensive analysis utilizing both descriptive qualitative and quantitative approaches, this study aimed to discern the impact of academic supervision on teachers' pedagogic competency in developing differentiated learning strategies. The data analysis demonstrated a discernible progression in pedagogic competency scores over the cycles. In the pre-cycle, scores were recorded at 44.17 with an average of 1.52, which subsequently increased to 65.44 with an average of 2.26 in cycle 1, and further elevated to 77.43 with an average of 2.67 in cycle 2. Similarly, an analogous advancement was observed in teachers' pedagogical competency scores for differentiated learning against predetermined standards, ascending from 38% in the pre-cycle to 69% in cycle 1, culminating in 97% in cycle 2. These findings substantiate the assertion that academic supervision plays a pivotal role in augmenting teachers' pedagogical competence, particularly in the context of developing differentiated learning methodologies.